Evaluasi Sistem Pengelolaan Limbah Jarum Suntik Medis: Studi Kasus di Unit Transfusi Darah - Rendi Ariyanto Sinanto; Sutrisno; Prayogo Sugio Purnomo (PT. Promosi Kesehatan Media, 2026)
ABSTRACT Background: Infectious waste is waste generated from medical facilities such as hospitals, community health centers, and polyclinics. It is a type of waste that falls into the biohazard category, meaning it is highly hazardous to the environment, containing many viruses, bacteria, and hazardous substances. Syringe waste is a type of medical waste consisting of used syringes used in various medical procedures, such as drug injections, blood sampling, vaccinations, and so on. This waste is categorized as B3 waste. The purpose of this study is to determine how syringe waste is managed at the Indonesian Red Cross (PMI) UTD (National Red Cross) in Yogyakarta City. Methods: This study employed a qualitative method. The approach used was a case study. A case study is a research method conducted by in-depth exploration of a program, event, process, or activity involving one or more people. This study employed a total sampling technique, involving the entire population as respondents. The analysis used was content analysis to describe and understand the meaning and patterns contained in the analyzed data. The points included transcription, coding, categories, themes, and interpretation. Results and Discussion: The results of this study indicate that the sorting, destruction, and transportation of syringe waste have been carried out effectively. However, the Yogyakarta City PMI UTD does not process syringe waste directly. The waste destruction process is outsourced to a third party, PT Global Nviro Nusa, while the transportation process is handled by a second party, PT Darindo. Conclusion: The management of syringe waste at the Yogyakarta City PMI UTD has been successful from sorting to transportation. However, the final destruction process is not carried out independently but rather delegated to external partners (PT Darindo and PT Global Nviro Nusa).